Subcutaneous Administration of Low-Molecular-Weight Heparin to Horses Inhibits Ex Vivo Equine Herpesvirus Type 1-Induced Platelet Activation - Stokol, Tracy; Serpa, Priscila B. S.; Brooks, Marjory B.; Divers, Thomas; Ness, Sally (Frontiers in Veterinary Science, 2018)
Equine herpesvirus type 1 (EHV-1) is a major cause of infectious respiratory disease, abortion and neurologic disease. Thrombosis in placental and spinal vessels and subsequent ischemic injury in EHV-1-infected horses manifests clinically as abortion and myeloencephalopathy. We have previously shown that addition of heparin anticoagulants to equine platelet-rich plasma (PRP) can abolish ex vivo EHV-1-induced platelet activation. The goal of this study was to test whether platelets isolated from horses treated with unfractionated heparin (UFH) or low-molecular-weight heparin (LMWH) were resistant to ex vivo EHV-1-induced activation. In a masked, block-randomized placebo-controlled cross-over trial, 9 healthy adult horses received 4 subcutaneous injections at q. 12 hour intervals of one of the following treatments: UFH (100 U/kg loading dose, 3 maintenance doses of 80 U/kg), 2 doses of LMWH (enoxaparin) 80 U/kg 24 hours apart with saline at the intervening 12 hour intervals, or 4 doses of saline. Blood samples were collected before treatment and after 36 hours, 40 hours (4 hours after the last injection) and 60 hours (24 hours after the last injection). Two strains of EHV-1, Ab4 and RacL11, were added to PRP ex vivo and platelet membrane expression of P selectin was measured as a marker of platelet activation. Drug concentrations were monitored in a Factor Xa inhibition (anti-Xa) bioassay. We found that LMWH, but not UFH, inhibited platelet activation induced by low concentrations (1 x 106 plaque forming units/mL) of both EHV-1 strains at 40 hours. At this time point, all horses had anti-Xa activities above 0.1 U/mL (range 0.15-0.48 U/mL) with LMWH, but not UFH. By 60 hours, a platelet inhibitory effect was no longer detected and anti-Xa activity had decreased (range 0.03 to 0.07 U/mL) in LMWH-treated horses. Neither heparin inhibited platelet activation induced by high concentrations (5 x 106 plaque forming units/mL) of the RacL11 strain. We found substantial between horse variability in EHV-1-induced platelet activation at baseline and after treatment. Minor injection site reactions developed in horses given either heparin. These results suggest that LMWH therapy may prevent thrombotic sequelae of EHV-1, however further evaluation of dosage regimens is required.